A semiconductor laser for non-hermetic applications
By setting a hydrophobic layer on the outer side of the urinary film and high-reverse film of the semiconductor laser and using ion beam assisted deposition technology, the problem of failure of semiconductor lasers in high temperature and high humidity environments is solved, and the packaging cost is reduced and the reliability of the laser is improved. Effect.
Patent Information
- Application Number
- CN202410819308.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-06-24
AI Technical Summary
Existing semiconductor lasers are prone to failure in high temperature and high humidity environments, resulting in reduced power and shortened service life, and require air-tight packaging to prevent water vapor from entering, increasing packaging costs.
The first and second hydrophobic layers are arranged on the outer side of the urinary film and the high-reverse film of the laser body, respectively, and plating is performed through ion beam-assisted deposition technology to ensure the density and adhesion of the hydrophobic layer and avoid water vapor entering.
Effectively prevent external water vapor from entering the laser, improve its reliability and life in high temperature and high humidity environments, so that semiconductor lasers can be applied to non-pneumatic packaging, reducing packaging costs.
Smart Images

Figure CN118748350B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a semiconductor laser for non-airtight applications, belonging to the technical field of lasers. Background Art
[0002] At present, the semiconductor lasers on the market are mainly used in hermetic applications. Hermetic applications refer to scenarios where the laser needs to be packaged in a nitrogen environment to work properly. The disadvantage of hermetic packaging is that the cost is very high. First of all, the process of hermetic packaging is relatively complicated. Compared with non-hermetic packaging, hermetic packaging requires the introduction of additional nitrogen, which increases the packaging cost; secondly, the process of hermetic packaging is relatively complicated, and operation and training are difficult, which increases labor costs. Finally, in terms of equipment, the equipment required for hermetic packaging is relatively expensive, and the equipment itself has high requirements for the environment, and other additional costs are also significantly increased. However, if the semiconductor laser itself can pass the high temperature and high humidity verification, then there is no need to use hermetic packaging, which can reduce the cost of module packaging and make the module more competitive in the market.
[0003] The reason why semiconductor lasers are prone to failure in high temperature and high humidity environments is that the two light-emitting end faces of the laser are easily affected by external water vapor, especially in high temperature and high humidity environments. Water vapor enters the laser through the end face film layer, resulting in reduced laser power and reduced service life. At present, the end face coating of semiconductor lasers generally uses electron beam thermal evaporation technology. The main advantage of this technology is simple equipment, but due to the instability of thermal evaporation coating, the film layer generally has a columnar structure. After the coating is completed, there may be holes in the film layer, which is very easy to absorb water. This further causes external water vapor to easily enter the two light-emitting end faces of the semiconductor laser, thereby affecting the performance of the semiconductor laser. Summary of the invention
[0004] The present invention provides a semiconductor laser for non-airtight applications, which can solve the problem that the existing semiconductor laser needs to be airtightly packaged, which leads to increased use costs.
[0005] The present invention provides a semiconductor laser for non-airtight applications, comprising:
[0006] The laser body has an anti-reflection film on its front cavity surface and a high-reflection film on its rear cavity surface;
[0007] A first hydrophobic layer is provided on the surface of the anti-reflection film away from the laser body, and is used to prevent external water vapor from entering the anti-reflection film;
[0008] A second hydrophobic layer is provided on the surface of the high-reflection film away from the laser body, and is used to prevent external water vapor from entering the high-reflection film;
[0009] The thickness of the second hydrophobic layer is greater than or equal to the thickness of the first hydrophobic layer.
[0010] Optionally, the first hydrophobic layer and the second hydrophobic layer are both deposited using ion beam assisted deposition technology.
[0011] Optionally, also include:
[0012] A first transition layer, disposed between the first hydrophobic layer and the anti-reflection film;
[0013] The lattice constant of the first transition layer is 50% to 150% of the lattice constant of the antireflection film.
[0014] Optionally, also include:
[0015] A second transition layer, disposed between the second hydrophobic layer and the high reflective film;
[0016] The lattice constant of the second transition layer is 50% to 150% of the lattice constant of the high-reflection film.
[0017] Optionally, the first transition layer and the second transition layer are both deposited using ion beam assisted deposition technology.
[0018] Optionally, both the first hydrophobic layer and the second hydrophobic layer are yttrium fluoride film layers.
[0019] Optionally, the thickness of the first hydrophobic layer is 7 nm to 13 nm; the thickness of the second hydrophobic layer is 12 nm to 18 nm.
[0020] Optionally, the thickness of the second transition layer is greater than or equal to the thickness of the first transition layer.
[0021] Optionally, both the first transition layer and the second transition layer are tantalum oxide film layers.
[0022] Optionally, the thickness of the first transition layer is 22nm-28nm; the thickness of the second transition layer is 37nm-43nm.
[0023] The beneficial effects that the present invention can produce include:
[0024] The semiconductor laser provided by the present invention provides a first hydrophobic layer on the outer side of the anti-reflection film of the laser body, and provides a second hydrophobic layer on the outer side of the high-reflection film, and limits the thickness of the second hydrophobic layer to be greater than or equal to the thickness of the first hydrophobic layer. In this way, while ensuring the normal light emission of the anti-reflection film side of the laser body, it is possible to prevent external water vapor from affecting the laser body to the greatest extent, thereby avoiding the cost increase caused by the airtight packaging.
[0025] The semiconductor laser provided by the present invention is provided with a first transition layer between the anti-reflection film and the first hydrophobic layer of the laser body, a second transition layer between the high-reflection film and the second hydrophobic layer, and IAD (ion beam assisted deposition technology) is used to assist plating of the first hydrophobic layer, the first transition layer on the anti-reflection film side, and the second hydrophobic layer and the second transition layer on the high-reflection film side. Since the anti-reflection film and the high-reflection film side are respectively provided with two layers of materials, the film layer as a whole has excellent optical properties and corrosion resistance. In addition, due to the characteristics of strong adhesion and high mechanical strength, the film layer is not easy to fall off and can pass most mechanical shock and vibration tests. Finally, the two film layers can also significantly improve the reliability of the laser. According to experimental results, the two film layers can completely prevent external water vapor from penetrating into the interior of the laser, effectively improving the life of the semiconductor laser in a high temperature and high humidity environment, so that the semiconductor laser can be applied to non-hermetic packaging, reducing the packaging cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A schematic diagram of the structure of a semiconductor laser for non-airtight applications provided by an embodiment of the present invention.
[0027] Reference numerals:
[0028] 10. Laser body; 11. Anti-reflection film; 12. First hydrophobic layer; 13. First transition layer; 14. High-reflection film; 15. Second hydrophobic layer; 16. Second transition layer. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with embodiments, but the present invention is not limited to these embodiments.
[0030] The embodiment of the present invention provides a semiconductor laser for non-airtight applications, such as Figure 1 As shown, including:
[0031] The laser body 10 has an anti-reflection film 11 disposed on its front cavity surface and a high-reflection film 14 disposed on its rear cavity surface.
[0032] The first hydrophobic layer 12 is disposed on the surface of the anti-reflection film 11 away from the laser body 10 , and is used to prevent external water vapor from entering the anti-reflection film 11 .
[0033] The second hydrophobic layer 15 is disposed on the surface of the high-reflection film 14 away from the laser body 10 , and is used to prevent external water vapor from entering the high-reflection film 14 .
[0034] The thickness of the second hydrophobic layer 15 is greater than or equal to the thickness of the first hydrophobic layer 12 .
[0035] The present invention arranges a first hydrophobic layer 12 on the outer side of the anti-reflection film 11 of the laser body 10, arranges a second hydrophobic layer 15 on the outer side of the high-reflection film 14, and limits the thickness of the second hydrophobic layer 15 to be greater than or equal to the thickness of the first hydrophobic layer 12. In this way, while ensuring the normal light emission of the anti-reflection film side of the laser body, it prevents external water vapor from affecting the laser body 10 to the greatest extent, thereby avoiding the cost increase caused by the airtight packaging.
[0036] In the embodiment of the present invention, the first hydrophobic layer 12 and the second hydrophobic layer 15 are both assisted by ion beam assisted deposition technology during film coating, which can reduce film voids in the first hydrophobic layer 12 and the second hydrophobic layer 15, improve the density and hydrophobicity of the film, and thus ensure the reliability of the semiconductor laser working in a high temperature and high humidity environment for a long time.
[0037] The embodiment of the present invention does not limit the specific materials of the first hydrophobic layer 12 and the second hydrophobic layer 15, and for example, they may be silicon dioxide or yttrium fluoride, etc. Since yttrium fluoride has better hydrophobicity, it is preferred that the first hydrophobic layer 12 and the second hydrophobic layer 15 are both yttrium fluoride film layers.
[0038] The embodiment of the present invention does not limit the specific thickness of the first hydrophobic layer 12 and the second hydrophobic layer 15, and those skilled in the art can determine the thickness by comprehensively considering factors such as hydrophobic performance, reflectivity of the anti-reflection film 11 and the high-reflection film 14. In practical applications, the thickness of the first hydrophobic layer 12 can be set to 7nm to 13nm, and for example, it can be 7nm, 10nm or 13nm; the thickness of the second hydrophobic layer 15 can be set to 12nm to 18nm, and for example, it can be 12nm, 15nm or 18nm.
[0039] Furthermore, the semiconductor laser also includes:
[0040] The first transition layer 13 is disposed between the first hydrophobic layer 12 and the anti-reflection film 11 ; the lattice constant of the first transition layer 13 is 50% to 150% of the lattice constant of the anti-reflection film 11 .
[0041] The second transition layer 16 is disposed between the second hydrophobic layer 15 and the high-reflection film 14 ; the lattice constant of the second transition layer 16 is 50% to 150% of the lattice constant of the high-reflection film 14 .
[0042] The present invention arranges a first transition layer 13 between the anti-reflection film 11 of the laser body 10 and the first hydrophobic layer 12. Since the first transition layer 13 and its substrate (i.e., the anti-reflection film 11) have a similar lattice constant, the adhesion of the first hydrophobic layer 12 is greatly enhanced. Similarly, a second transition layer 16 is arranged between the high-reflection film 14 and the second hydrophobic layer 15. Since the second transition layer 16 and its substrate (i.e., the high-reflection film 14) have a similar lattice constant, the adhesion of the second hydrophobic layer 15 is greatly enhanced. In this way, the overall mechanical strength of the film layer is improved, the film layer is not easy to fall off, and can pass most mechanical shock and vibration tests.
[0043] Preferably, the first transition layer 13 and the second transition layer 16 are both ion beam assisted deposition technology used for film coating. This can reduce film voids in the first transition layer 13 and the second transition layer 16, improve the density and hydrophobicity of the film, and thus ensure the reliability of the semiconductor laser working in a high temperature and high humidity environment for a long time.
[0044] The embodiment of the present invention does not limit the specific materials of the first transition layer 13 and the second transition layer 16, and examples thereof may be silicon or tantalum oxide, etc. Since tantalum oxide has better hydrophobicity, preferably, the first transition layer 13 and the second transition layer 16 are both tantalum oxide film layers.
[0045] The embodiment of the present invention does not limit the specific thickness of the first transition layer 13 and the second transition layer 16, and those skilled in the art can determine the thickness by comprehensively considering factors such as hydrophobic performance, the reflectivity of the anti-reflection film 11 and the high-reflection film 14. In practical applications, the thickness of the second transition layer 16 is greater than or equal to the thickness of the first transition layer 13, and the thickness of the first transition layer 13 is 22nm to 28nm, and can be 22nm, 25nm or 28nm, etc. by way of example; the thickness of the second transition layer 16 is 37nm to 43nm, and can be 37nm, 40nm or 43nm, etc. by way of example.
[0046] The following is an explanation of the manufacturing materials, film thickness, and plating assist process selection of the first hydrophobic layer 12 , the second hydrophobic layer 15 , the first transition layer 13 , and the second transition layer 16 through experiments.
[0047] (1) Membrane material selection experiment.
[0048] Adding a transition layer and a hydrophobic layer on the basis of the anti-reflection film 11 and the high-reflection film 14, first of all, the appropriate coating material should be selected. The transition layer must have a lattice constant close to that of the substrate, and the hydrophobic layer must have a relatively good hydrophobic property, that is, the hydrophobic layer needs to have a lower failure rate under the same thickness, so that more semiconductor lasers can pass the high temperature and high humidity verification. The main coating materials and parameters of the transition layer and the hydrophobic layer are shown in Table 1.
[0049] Table 1 Main coating materials and parameters
[0050] Coating materials Coating rate None (control group) Si 1nm / s <![CDATA[SiO2]]> 0.5nm / s <![CDATA[Ta2O5]]> 0.5nm / s <![CDATA[Yttrium fluoride (YF3)]]> 1nm / s
[0051] The laser chip was subjected to a high temperature and high humidity (humidity 85%, temperature 85°C) experiment, and the experiment was divided into the following five groups.
[0052] The first group is the control group: after the chips are normally coated, 200 chips are randomly selected.
[0053] The second group is the experimental group: after the normal coating of the two end faces of the chip is completed, 5nm Si is plated first, and then 5nm SiO2 is plated, and 200 chips are randomly selected.
[0054] The third group is the experimental group: after the normal coating of the two end faces of the chip is completed, 5nm Si is plated first, and then 5nm YF3 is plated, and 200 chips are randomly selected.
[0055] The fourth group is the experimental group: after the normal coating of the two end faces of the chip is completed, 5nm Ta2O5 is first plated, and then 5nm SiO2 is plated, and 200 chips are randomly selected.
[0056] The fifth group is the experimental group: after the normal coating of the two end faces of the chip is completed, 5nm Ta2O5 is plated first, and then 5nm YF3 is plated, and 200 chips are randomly selected.
[0057] After 100 hours of high temperature and high humidity experiment, the change of threshold current of each laser chip was recorded, and the failure rate of each group was counted. The results are shown in Table 2.
[0058] Table 2 Failure ratio of each group after 100h high temperature and high humidity test
[0059] Coating materials 100h failure rate None (control group) 96% <![CDATA[Si+SiO2]]> 78.5% <![CDATA[Si+YF3]]> 66% <![CDATA[Ta2O5+SiO2]]> 84% <![CDATA[Ta2O5+YF3]]> 46.5%
[0060] From the above data, it can be seen that the failure rate of the outermost layer Ta2O5+YF3 is significantly lower than that of the other four groups of experiments, which shows that Ta2O5+YF3 has better hydrophobic performance. Therefore, subsequent experiments use Ta2O5+YF3 as the material of the transition layer + hydrophobic layer for verification.
[0061] (2) Film thickness selection experiment.
[0062] After the film material is determined, the coating should also select a suitable coating thickness based on the anti-reflection film 11 and the high-reflection film 14 in order to ensure that the reflectivity is within the tolerance range. The reflectivity of the anti-reflection film 11 (1% ± 0.02) and the reflectivity of the high-reflection film 14 (90% ± 2%) have different tolerances, so the anti-reflection film 11 and the high-reflection film 14 are verified separately.
[0063] 1) Anti-reflection film 11 reflectivity verification experiment.
[0064] The main process parameters of the first transition layer 13 and the first hydrophobic layer 12 on the anti-reflection film side are shown in Table 3.
[0065] Table 3 Main process parameters of the side film layer of the anti-reflection film
[0066]
[0067]
[0068] The anti-reflection film side layer reflectivity verification experiment is divided into the following five groups.
[0069] The first group is the control group: after the chip is normally coated, the reflectivity of the anti-reflection film 11 is tested.
[0070] The second group is the experimental group: after the chip anti-reflection film 11 is normally coated, 25nm Ta2O5 is first coated, and then 10nm YF3 is coated, and the reflectivity of the anti-reflection film 11 is tested.
[0071] The third group is the experimental group: after the chip anti-reflection film 11 is normally coated, 25nm Ta2O5 is first coated, and then 20nm YF3 is coated, and the reflectivity of the anti-reflection film 11 is tested.
[0072] The fourth group is the experimental group: after the chip anti-reflection film 11 is normally coated, 50nm Ta2O5 is first coated, and then 10nm YF3 is coated, and the reflectivity of the anti-reflection film 11 is tested.
[0073] The fifth group is the experimental group: after the chip anti-reflection film 11 is normally coated, 50nm Ta2O5 is first coated, and then 20nm YF3 is coated, and the reflectivity of the anti-reflection film 11 is tested.
[0074] Table 4 Reflectivity of the antireflection coating of each group
[0075] <![CDATA[Ta2O5 + YF3 thickness]]> AR coating reflectivity None (control group) 1% 25nm+10nm 1.01% 25nm+20nm 0.95% 50nm+10nm 1.24% 50nm+20nm 2.02%
[0076] It can be seen from Table 4 that the reflectivity of first coating with 25nm Ta2O5 and then coating with 10nm YF3 is within the reflectivity tolerance range of the anti-reflection film 11, and the other experimental groups do not meet the film reflectivity requirements, so subsequent experiments use 25nm Ta2O5+10nm YF3 as the thickness of the first transition layer 13 and the first hydrophobic layer 12 on the anti-reflection film side for verification.
[0077] 2) High reflectivity verification experiment of high reflective film 14.
[0078] The experiment was divided into the following five groups.
[0079] The first group is the control group: after the chip is normally coated, the reflectivity of the high-reflective film 14 is tested.
[0080] The second group is the experimental group: after the normal coating of the chip high-reflection film 14 is completed, 40nm Ta2O5 is first coated, and then 5nm YF3 is coated to test the reflectivity of the high-reflection film 14.
[0081] The third group is the experimental group: after the normal coating of the chip high-reflection film 14 is completed, 40nm Ta2O5 is first coated, and then 15nm YF3 is coated to test the reflectivity of the high-reflection film 14.
[0082] The fourth group is the experimental group: after the normal coating of the chip high-reflection film 14 is completed, 80nm Ta2O5 is first coated, and then 5nm YF3 is coated to test the reflectivity of the high-reflection film 14.
[0083] The fifth group is the experimental group: after the normal coating of the chip high-reflection film 14 is completed, 80nm Ta2O5 is first coated, and then 15nm YF3 is coated to test the reflectivity of the high-reflection film 14.
[0084] Table 5 Reflectivity of high reflective film in each group
[0085] <![CDATA[Ta2O5 + YF3 thickness]]> High reflectivity None (control group) 90% 40nm+5nm 92.5% 40nm+15nm 90.8% 80nm+5nm 87.2% 80nm+15nm 86.1%
[0086] It can be seen from Table 5 that the reflectivity of first coating with 40nm Ta2O5 and then coating with 15nm YF3 is within the reflectivity tolerance range of the high-reflectivity film 14. The other experimental groups do not meet the film reflectivity requirements, so subsequent experiments use 40nm Ta2O5+15nm YF3 as the thickness of the second transition layer 16 and the second hydrophobic layer 15 on the high-reflectivity film side for verification.
[0087] (3) Electroplating process verification experiment.
[0088] The anti-reflection film side is coated with 25nm Ta2O5+10nmYF3, and the high-reflection film side is coated with 40nm Ta2O5+15nmYF3. When plating Ta2O5 and YF3, the ion beam is used as an auxiliary bombardment film to make the film dense and uniform, reduce the voids in the film, and the structure has higher hydrophobicity, which can effectively prevent water vapor from entering the chip through the film in high temperature and high humidity environments, thereby improving the chip life. The main parameters of the ion source assisted plating process are shown in Table 6.
[0089] Table 6 Main process parameters of ion source
[0090] Main parameters of ion source plating Reference range Accelerating voltage 200V Ion beam retention 3A Bombardment Angle 30°
[0091] The laser chip was subjected to a high temperature and high humidity (humidity 85%, temperature 85°C) experiment, and the experiment was divided into the following three groups.
[0092] The first group is the control group: after the normal coating of the chips is completed, 200 chips are randomly selected;
[0093] The second group is the experimental group: after the two end faces of the chip are coated, the anti-reflection film side is coated with 25nm Ta2O5+10nmYF3. The high-reflection film side is coated with 40nm Ta2O5+15nmYF3. 200 chips are randomly selected;
[0094] The third group is the experimental group: after the two end faces of the chip are coated, the anti-reflection film side is coated with 25nm Ta2O5+10nmYF3. The high-reflection film side is coated with 40nm Ta2O5+15nmYF3, and IAD is used to assist in the coating of Ta2O5 and YF3. 200 chips are randomly selected;
[0095] After 2000h of high temperature and high humidity experiment, the changes in the threshold current of each laser chip were recorded, and the failure rate of each group was counted.
[0096] Table 7 Failure ratio of each group after 2000h high temperature and high humidity test
[0097] Outer material and process Failure rate None (control group) 99.5% <![CDATA[Ta2O5+YF3]]> 21.5% <![CDATA[Ta2O5 + YF3 + IAD Fluxing]]> 0%
[0098] It can be seen from Table 7 that the use of Ta2O5+YF3+IAD plating aids for the outermost layer can completely prevent water vapor from entering the laser through the end face, greatly improving the life of the chip in high temperature and high humidity environments.
[0099] The present invention overcomes the shortcomings of traditional thermal evaporation film layers in non-airtight semiconductor laser cavity surface coating, and proposes to add a layer of Ta2O5 with similar stress as a transition layer on the original anti-reflection film 11 and high-reflection film 14, and add another layer of YF3 outside the Ta2O5 as the outermost hydrophobic layer. The combination of two layers of materials and the selection of a suitable film thickness will greatly improve the optical properties and corrosion resistance of the film. The presence of the transition layer will also greatly enhance the adhesion of the film, while improving the overall mechanical strength of the film, making it difficult for the film to fall off, and can pass most mechanical shock and vibration tests. Finally, while coating, an ion beam is introduced to assist the coating of the two outer layers of the film, which can further reduce the voids in the film, improve the density and hydrophobicity of the cavity surface film layer, and improve the reliability of the chip working in a high temperature and high humidity environment for a long time. It has been verified in experiments and achieved good results.
[0100] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A semiconductor laser for non-airtight applications, characterized in that: include: The laser body has an anti-reflection film on its front cavity surface and a high-reflection film on its rear cavity surface; A first hydrophobic layer is provided on the surface of the anti-reflection film away from the laser body, and is used to prevent external water vapor from entering the anti-reflection film; A second hydrophobic layer is provided on the surface of the high-reflection film away from the laser body, and is used to prevent external water vapor from entering the high-reflection film; the thickness of the second hydrophobic layer is greater than or equal to the thickness of the first hydrophobic layer; the first hydrophobic layer and the second hydrophobic layer are both yttrium fluoride film layers; A first transition layer is disposed between the first hydrophobic layer and the anti-reflection film; the lattice constant of the first transition layer is 50% to 150% of the lattice constant of the anti-reflection film; The second transition layer is arranged between the second hydrophobic layer and the high-reflective film; the lattice constant of the second transition layer is 50% to 150% of the lattice constant of the high-reflective film.
2. The semiconductor laser according to claim 1, characterized in that The first hydrophobic layer and the second hydrophobic layer are both deposited using ion beam assisted deposition technology.
3. The semiconductor laser according to claim 1, characterized in that The first transition layer and the second transition layer are both deposited using ion beam assisted deposition technology.
4. The semiconductor laser according to claim 1, characterized in that The thickness of the first hydrophobic layer is 7nm-13nm; the thickness of the second hydrophobic layer is 12nm-18nm.
5. The semiconductor laser according to claim 1, characterized in that The thickness of the second transition layer is greater than or equal to the thickness of the first transition layer.
6. The semiconductor laser according to claim 1, characterized in that The first transition layer and the second transition layer are both tantalum oxide film layers.
7. The semiconductor laser according to claim 1 or 6, characterized in that: The thickness of the first transition layer is 22nm-28nm; the thickness of the second transition layer is 37nm-43nm.
Citation Information
Patent Citations
Intelligent low-emissivity coated glass capable of offline tempering and preparation method thereof
CN102910837A
Laser assembly with temperature compensation function
CN113972559A
Semiconductor laser with hydrophobic cavity surface and manufacturing method thereof
CN117498147A
Semiconductor laser device
US20070053398A1